User Experiences While Playing Dance-Based Exergames and the Influence of Different Body Motion Sensing Technologies - Alasdair G. Thin; Craig Brown; Paul Meenan (International Journal of Computer Games Technology)
Dance Dance Revolution is a pioneering exergame which has attracted considerable interest for its potential to promote regular exercise and its associated health benefits. The advent of a range of different consumer body motion tracking video game console peripherals raises the question whether their different technological affordances (i.e., variations in the type and number of body limbs that they can track) influence the user experience while playing dance-based exergames both in terms of the level of physical exertion and the nature of the play experience. To investigate these issues a group of subjects performed a total of six comparable dance routines selected from commercial dance-based exergames (two routines from each game) on three different consoles. The subjects’ level of physical exertion was assessed by measuring oxygen consumption and heart rate. They also reported their perceived level of exertion, difficulty, and enjoyment ratings after completing each dance routine. No differences were found in the physiological measures of exertion between the peripherals/consoles. However, there were significant variations in the difficulty and enjoyment ratings between peripherals. The design implications of these results are discussed including the tension between helping to guide and coordinate player movement versus offering greater movement flexibility.